KAJI EKSPERIMEN MODEL PATAHAN PADA AL 6061 – ABU DASAR BATU BARA YANG MENDAPAT PERLAKUAN PANAS - Achmad, Zainun (MEKANIKA: Jurnal Teknik Mesin, 2015)
Composite is a blend of two materials or that have a different phase becoming a new material, which has better properties than both. If fusion is occurring microscopic (molecular level) then referred to as alloy / blend.This study aims to analyze the surface of the fatigue test results using Macro photograph and SEM-EDX. In thisstudy was observed fracture fatigue test results. To determine the morphology of each treatment and no treatment.Conclusions testing fatigue fracture surface photograph can find out which models are tired of the results of afatigue fracture. The method is used, using the test results broken fatigue rotary bending fatigue fracture by taking alook at the best cycle. Then, after the material was broken in doing observations mikroskope photo to view themicrostructure and phase formed from each treatment and without heat treatment, after it is done using the STEMIDV4 macro image to see the surface of the account after break tired. And to see perpatan composition using SEMEDXInspect S50 to see the line and the composition of the material that gets the heat treatment and withoutsediment heat treatment.Keywords: Composites, fatigue fracture fatigue, Structure mikroskope, Photo Macro, SEM-EDX